2017
DOI: 10.1055/s-0037-1604363
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Insipidus following Endoscopic Transsphenoidal Surgery for Pituitary Adenoma

Abstract: Pituitary adenoma (PA), among the most commonly encountered sellar pathologies, accounts for 10% of primary intracranial tumors. The reported incidence of postoperative diabetes insipidus (DI) is highly variable. In this study, we report our experience with DI following endoscopic transsphenoidal surgery (TSS) for PAs, elucidating the risk factors of postoperative DI, the likelihood of long-term DI, and the impact of DI on the length of stay (LOS). The study included 178 patients who underwent endoscopic resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…A previous retrospective study found delayed hyponatremia to be the most common cause for readmission, followed by DI [13]. Other reports have noted occurrence of early transient DI after TSS ranging from 10-60% [2,31,32]. In the present study, transient DI occurred in 35.5% of the delayed hyponatremia cases and in 8.5% of cases with normal natremia, while multivariate analysis showed that transient DI was signi cantly correlated with delayed hyponatremia (OR 6.21, p = 0.001) as was meningitis (OR 12.03, p = 0.006).…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study found delayed hyponatremia to be the most common cause for readmission, followed by DI [13]. Other reports have noted occurrence of early transient DI after TSS ranging from 10-60% [2,31,32]. In the present study, transient DI occurred in 35.5% of the delayed hyponatremia cases and in 8.5% of cases with normal natremia, while multivariate analysis showed that transient DI was signi cantly correlated with delayed hyponatremia (OR 6.21, p = 0.001) as was meningitis (OR 12.03, p = 0.006).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Moreover, there was no intraoperative CSF leak and most significantly postoperative MRI was normal. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of DI ranges from 0.3-45% and is variable in part because of inconsistent definitions [95]. Two experienced pituitary groups who used accepted definitions for DI and whose surgical experience predominantly focused on endoscopic resection of pituitary adenomas have recently published their postoperative DI rates with fairly comparable results [96,97]. In 178 and 271 patients respectively, both studies Frontiers in Clinical Neurosurgery reported a DI incidence rate of 26% and 16.6% with only 10% and 4% progressing to permanent DI [96,97].…”
Section: Complicationsmentioning
confidence: 99%